2002
DOI: 10.4161/cc.1.5.152
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Caspase-3 and -7 Does Not Correlate with the Extent of Apoptosis in Primary Breast Carcinomas

Abstract: Association between the rate of apoptosis and expression of the several relevant molecules (Bcl-2, pro-and active caspase-3, and caspase-7) was studied in 61 primary breast carcinomas. The rate of apoptosis detected both morphologically and by the TUNEL assay appeared to be high in 18 (30%), moderate in 14 (23%), and low in 29 (48%) carcinomas. High apoptotic index was strongly associated with advanced tumor grade and estrogen receptor positive (ER+) status but not with other investigated clinical or morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…As shown in Figure 5b, pentamidine induced pro-apoptotic caspase3/7 over-expression, causing the EBV positive B cells to undergo apoptosis in a dose-dependent manner (Figure 5c). However, the correlation of caspase 3/7 expression level and the extent of apoptosis was not observed, which had been also documented by previous reports [25], [26]. Inhibition of positive B cells proliferation with an IC 50 of 23.4±6.1 µM was observed (Figure 5d).…”
Section: Resultssupporting
confidence: 86%
“…As shown in Figure 5b, pentamidine induced pro-apoptotic caspase3/7 over-expression, causing the EBV positive B cells to undergo apoptosis in a dose-dependent manner (Figure 5c). However, the correlation of caspase 3/7 expression level and the extent of apoptosis was not observed, which had been also documented by previous reports [25], [26]. Inhibition of positive B cells proliferation with an IC 50 of 23.4±6.1 µM was observed (Figure 5d).…”
Section: Resultssupporting
confidence: 86%
“…In vivo work has revealed that apoptosis of breast cancer cells rapidly increases to a peak after chemotherapy, and then rapidly declines to baseline levels with an increase in the apoptotic index from 2.5% at baseline to over 20% following treatment (28)(29)(30). These studies suggest that apoptosis may be a significant contributor to treatment-induced cell death.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, determining the importance of therapy-induced apoptosis in solid tumors currently remains a relatively unexplored area of clinical research. Similarly, the evidence for a spontaneous apoptosis and its relationship with other tumor-related biological features have not been extensively investigated (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, dysregulation of apoptosis observed in some studies seems to be much more complex, and does not allow for simple conclusions. Expression of caspase-3 and -7 did not correlate with clinico-pathological features of breast cancer [432], and active caspase-6 concentrations were increased in progressive melanoma and its metastases compared to non-malignant naevi [433]. Therefore, despite the fact that disturbances of apoptosis regulation in various tumors are obvious, there is still no certainty regarding the problem whether these disturbances are primary or secondary events in cancer [407].…”
Section: Resistance To Apoptosis and Tumor "Counter Attack"mentioning
confidence: 84%